Oligocene Ailanthus from northwestern Qaidam Basin, northern Tibetan Plateau, China and its implications. (23rd June 2020) - Yang, Tao; Jia, Jingwei; Chen, Hongyu; Zhang, Yuxin; Wang, Yong; Wang, Haojian; Bao, Lin; Zhang, Li; Li, Wenjia; Xie, Sanping; Yan, Defei
Abstract : As the largest inland basin in the northeastern Tibetan Plateau, Qaidam Basin has traditionally been thought of as the key region to study the Cenozoic climatic changes in the plateau; however, the information from a palaeobotanic respect is still lacking because of the paucity of the fossil plants. Fossil fruits and foliage of Ailanthus (Simaroubaceae) are reported from the Oligocene Shangganchaigou Formation in the northwestern Qaidam Basin, Qinghai Province, China. All the characters suggest that the fossil materials should be assigned to A . confucii, which is one widely distributed fossil species in the Cenozoic, regarded as the analogue of extant A. altissima . Current materials represent the first fossil record of Simaroubaceae in the northern Tibetan Plateau. Based on the climate requirements of the living A. altissima, the ranges of mean annual temperature (MAT) and mean annual precipitation (MAP) reflected by current fossils from Qaidamare 6.9–17.0°C, and 376–1, 383 mm, respectively, compared with the current climate at the fossil site with MAT of −1.03°C and MAP of 60.5 mm. The results indicate that the climate conditions of the fossil site during the Early Oligocene were much warmer and more humid than that of the current. We hereby suggest the warm and moist air could approach the northwestern Qaidam and to accommodate the ecological environment in Early Oligocene.